Ecological and behavioural traits of the Sri Lankan water monitor (Varanus salvator) in an urban landscape of Western Province, Sri Lanka - Karunarathna, S.; Surasinghe, T.; Madawala, M.; Somaweera, Ruchira; Amarasinghe, A. (CSIRO Publishing, 2017)
The Asian water monitor Varanus salvator is one of the largest species of lizard in the world and is widespread on the island of Sri Lanka. In the present study, we conducted a 7-month survey within a 5-km stretch in the urbanised Attanagalu-Oya river area to study habitat associations, mesohabitat use and behaviour of V. salvator in urban landscapes. The greatest number of monitor sightings was made in aquatic habitats, followed by terrestrial and arboreal habitats within the riparian zone. Sightings of different life history stages of V. salvator across major habitat types varied significantly. The adults and subadults associated mostly with aquatic and terrestrial habitats, whereas hatchlings and juveniles associated mostly with aquatic and arboreal habitats. Given variable sighting frequencies of distinct life history stages across different major habitat types, it is likely that there is substantial age-structured niche partitioning in V. salvator. The urban population of V. salvator studied seemed to be fairly abundant, and resilient to anthropogenic stressors and adversity of urbanisation. In species-depauperate urban environments, ecosystem functions provisioned by V. salvator as generalist predators as well as scavengers are arguably significant and deserve further investigation. No direct anthropogenic threats were observed during the study.